Measuring Vestibular Contributions to Age-Related Balance Impairment: A Review - Wagner, Andrew R.; Akinsola, Olaoluwa; Chaudhari, Ajit M. W.; Bigelow, Kimberly E.; Merfeld, Daniel M. (Frontiers in Neurology, 2021)
Aging is associated with progressive declines in both the vestibular and human balance systems. While vestibular lesions certainly contribute to imbalance, the specific contributions of age-related vestibular declines to age-related balance impairment is poorly understood. This gap in knowledge results from the absence of a standardized method for measuring age-related changes to the vestibular balance pathways. The purpose of this manuscript is to provide an overview of the existing body of literature as it pertains to the methods currently used to infer vestibular contributions to age-related imbalance.